The Revival of the Russian Literary Avantgarde The Thaw Generation and Beyond - Kolchinsky, Irene E. (Slavistische Beitraege, 2001)
This study is devoted to the authors who initiated the revival of the Russian avantgarde tradition, which had been brutally suppressed by the Soviet authorities in the mid- 1930s. The revival of this tradition took place in the literary underground, where writers who endeavored to fulfil this challenging task largely remained until the collapse of the Soviet regime. Most of them emerged from obscurity only at the beginning of the 1990s, which explains why their dramatic and fascinating history has been so little examined by scholars. Although the situation has changed significantly in the last decade, during which some insightful studies have appeared in both Russia and the West, the subject obviously requires more thorough and systematic exploration. This book aims to narrow important gaps in the scholarship on the Russian literary avantgarde during its least investigated period.